2017
DOI: 10.1149/2.0451713jes
|View full text |Cite
|
Sign up to set email alerts
|

3D Failure Analysis of Pure Mechanical and Pure Chemical Degradation in Fuel Cell Membranes

Abstract: Lifetime-limiting failure of fuel cell membranes is generally attributed to their chemical and/or mechanical degradation. Although both of these degradation modes occur concurrently during operational duty cycles, their uncoupled investigations can provide useful insights into their individual characteristics and consequential impacts on the overall membrane failure. X-ray computed tomography is emerging as an advantageous tool for fuel cell failure analysis due to its non-destructive and non-invasive 3D imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…Symmetrical branching was predicted, and it was in good agreement with the experimental observations found in the literature. But at the same time, they also pointed out that the size of the specimen and the type of material may relevantly influence the crack path, which was confirmed by Singh, Orfino, Dutta, and Kjeang () in a research on the failure analysis of fuel cell membranes handled with chemical or mechanical degradations. It was found that bifurcation cracks occurred only when mechanical degradation and chemical degradation acted simultaneously, which was explained that the material embrittlement caused by chemical degradation makes cracks easier to propagate.…”
Section: Discussionmentioning
confidence: 70%
“…Symmetrical branching was predicted, and it was in good agreement with the experimental observations found in the literature. But at the same time, they also pointed out that the size of the specimen and the type of material may relevantly influence the crack path, which was confirmed by Singh, Orfino, Dutta, and Kjeang () in a research on the failure analysis of fuel cell membranes handled with chemical or mechanical degradations. It was found that bifurcation cracks occurred only when mechanical degradation and chemical degradation acted simultaneously, which was explained that the material embrittlement caused by chemical degradation makes cracks easier to propagate.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, from the perspective of cell durability, several researchers reported that cracks in the CL reduces cell durability [ 30 , 31 , 32 ]. Consequently, it is desirable to study the ink exhaling method that suppresses the occurrence of cracks.…”
Section: Resultsmentioning
confidence: 99%
“…Aindow et al [ 17 ] simulated the stress state of PEM during humidity cycle by ex-situ mechanical fatigue experiment, drew the stress cycle failure curve to predict the mechanical durability of the membrane under humidity cycle, and predicted the residual life of PEM by comparing the fatigue test data of the initial and the degraded samples. Singh et al [ 18 , 19 ] induced the pure mechanical membrane degradation by 0%–90% RH cycling accelerated test, that indicates a high crossover leakage near the gas inlet (as shown in Figure 2 ), which is indicator of preferentially severe mechanical degradation. At the same time, it was found that the cracks in the catalyst layer (especially the cracks on the cathode side) have a high mechanical stress concentration effect on the PEM contacting with it, which promotes the crack propagation of PEM.…”
Section: The Degradation Of Proton Exchange Membranementioning
confidence: 99%